2019
DOI: 10.5114/jcb.2019.84419
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anatomical position of point B and the relationship between point B dose and the dose delivered to pelvic lymph nodes in CT-based high-dose-rate brachytherapy for uterine cervical cancer

Abstract: Purpose To examine the anatomical position of point B and the relationship between the dose at point B and the dose delivered to the pelvic lymph nodes in computed tomography (CT)-based brachytherapy for cervical cancer. Material and methods Forty-nine cervical cancer patients were treated at Kyushu University Hospital. For all cases, planning CT images obtained after the applicator insertion were imported to an Oncentra Brachy (Elekta AB, Stockholm, Sweden), and points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Matsukawa et al correlated dose to point B with dose to the pelvic lymph nodes using two applicators used in ICBT. They found that the dose delivered to point B and the PLN groups were not significantly different between TO and tandem and cylinder [12]. Similarly, we observed there was no difference in the median EQD2 to the pelvic lymph nodes across the three applicators.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Matsukawa et al correlated dose to point B with dose to the pelvic lymph nodes using two applicators used in ICBT. They found that the dose delivered to point B and the PLN groups were not significantly different between TO and tandem and cylinder [12]. Similarly, we observed there was no difference in the median EQD2 to the pelvic lymph nodes across the three applicators.…”
Section: Discussionsupporting
confidence: 73%
“…Similar studies have been done by Chua et al [8], Lee et al [11], Lee Y et al [12] and Matsukawa et al [13], where they did CT based planning but prescribed to point A.…”
Section: Discussionsupporting
confidence: 66%
“…This finding identifies another method of delineating the lymph nodes in brachytherapy for cervical cancer, that is, delineating the overall lymph node area. Matsukawa et al 16 . reported that among 49 patients with cervical cancer treated with brachytherapy, the obturator lymph node group dose was 53% of the point B dose, the internal iliac lymph node group was 22% of the point B dose, and there was a strong dose correlation between the D 50 in obturator lymph node group and point B.…”
Section: Discussionmentioning
confidence: 99%